Remote Lifestyle Coaching Plus a Connected Glucose Meter with Certified Diabetes Educator Support Improves Glucose and Weight Loss for People with Type 2 Diabetes - Jennifer B. Bollyky; Dena Bravata; Jason Yang; Mark Williamson; Jennifer Schneider (Journal of Diabetes Research)
Background. Connected health devices with lifestyle coaching can provide real-time support for people with type 2 diabetes (T2D). However, the intensity of lifestyle coaching needed to achieve outcomes is unknown. Methods. Livongo provides connected, two-way messaging glucose meters, unlimited blood glucose (BG) test strips, and access to certified diabetes educators. We evaluated the incremental effects of adding lifestyle coaching on BG, estimated HbA1c, and weight. We randomized 330 eligible adults (T2D, HbA1c > 7.5%, BMI ≥ 25) to receive no further intervention (n=75), a connected scale (n=115), scale plus lightweight coaching (n=73), or scale plus intense coaching (n=67) for 12 weeks. We evaluated the change in outcomes using ANOVA. Results. Livongo participation alone resulted in improved BG control (mean HbA1c declined: 8.5% to 7.5%, p=0.01). Mean weight loss and additional BG decreases were higher in the intensive compared with the lightweight coaching and scale-only groups (weight change (lb): −6.4, −4.1, and −1.1, resp., p=0.01; BG change (mg/dL): −19.4, −11.3, and −2.9, resp., p=0.02). The estimated 12-week program costs were 5.5 times more for intensive than lightweight coaching. Conclusion. Livongo participation significantly improves BG control in people with T2D. Additional lifestyle coaching may be a cost-effective intervention to achieve further glucose control and weight loss.